Fabrication of agave tequilana bagasse/PLA composite and preliminary mechanical properties assessment - Huerta-Cardoso, Omar; Durazo-Cardenas, Isidro; Longhurst, Philip J.; Simms, Nigel J.; Encinas-Oropesa, Adriana (Elsevier, 2020)
Bagasse agave tequilana fibres (ATF), an abundant by-product of Mexican tequila production, were characterised, treated and investigated as a reinforcement and filler material for polylactic acid (PLA) green composites. Two fibre pre-treatments were investigated: alkali (8% NaOH solution) and enzymatic (0.4% Pectate lyase solution). Composites pellets of 20, 40 and 60% (w/v) of ATF in PLA were manufactured using extrusion moulding. Press moulding was used to fabricate samples composite plates. Tensile, flexural, impact and water absorption properties were investigated on machined samples. Assessment of the mechanical properties showed tensile strength of up to 57.1 MPa for 20 % (w/v) of ATF untreated samples. Flexural strength up to 98.8 MPa and impact strength of 6.8 kJ/m2 for 40% (w/v) of ATF alkali treated samples. These values compare well with those of other new bio-composites. The values of the Young’s and flexural moduli are in proximity, if not superior, to those of widely used polymers PLA and GPPS. The optimal ATF loading was found to be ∼40%. Alkali treatment of fibres provided marginally improved mechanical properties; while significantly increasing the samples’ water absorption. Microscopy observations confirmed the two pre-treatments enhanced the fibre/matrix adhesion when compared with untreated fibres.
Keywords: Natural fibres-based composites; Agave bagasse; PLA; Compression moulding